An unusual presentation of choriocarcinoma - Rao, Amishrita Lakku; Devi, Rama Sarala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Choriocarcinoma is the most malignant growth arising from the uterine body. Incidence of choriocarcinoma following vesicular mole is 29-83%. Diagnosis of choriocarcinoma is by histopathology only. In the present case 22year old woman with history of vesicular mole evacuation 8 months back suddenly landed in shock. During her irregular follow up, misleading ultrasonographic findings and clinical features delayed the diagnosis of advanced choriocarcinoma till it perforated through the uterus and patient landed in shock due to massive hemoperitoneum. We report this case because of its unusual presentation which led to diagnostic dilemma and mismanagement.